Stakeholder Capacity Building For Sustainable Tourism In Lumbok Seminung, West Lampung - Dedy Hermawan; Rahayu Sulistiowati; Nana Mulyana; Meiliyana; Susana Indriyati Caturiani; Dewie Brima Atika; Suprihatin Ali; Dadang Karya Bakti; Anisa Utami S. (CITAKARYA Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to enhance stakeholder capacity particularly youth in Lumbok Seminung District, West Lampung Regency, in the areas of administrative management, sustainable tourism management, and digital marketing to support the development of the Lumbok Seminung Thematic Market. The main partner problems include weak administrative systems, limited understanding of sustainable tourism principles, and low utilization of digital technology for promotion. The activity was implemented through three stages: preparation (literature review and initial observation), implementation (training and mentoring), and evaluation and reporting. Training materials encompassed business administration, entrepreneurship, leadership, and practical digital marketing content creation. Results indicate improved participant understanding and skills in managing thematic market administration and utilizing digital platforms for tourism promotion. A multi-stakeholder collaborative approach involving higher education institutions, local government, and local communities proved effective in building stakeholder capacity for sustainable tourism development in the Lumbok Seminung area.